2003
DOI: 10.1208/ps050105
|View full text |Cite
|
Sign up to set email alerts
|

A mucoadhesive, cyclodextrin-based vaginal cream formulation of itraconazole

Abstract: KEYWORDSItraconazole, vaginal, cyclodextrin, mucoadhesive, toxicity, clinical investigation, candidiasisThe development of vaginal medications, especially antifungal medications, requires that the drug is solubilized as well as retained at or near the mucosa for sufficient periods of time to ensure adequate bioavailability. Itraconazole is a broad-spectrum antifungal agent, which has been used for some time orally and intravenously but for which a vaginal formulation has not yet been developed. We present here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…The aqueous solubility of itraconazole at ambient temperature and neutral pH was recoded to be around 1 ng/ml. The solubility was found to undergo significant increase in acidic solution reaching 4 μg/ml in 0.1 N HCl at 25°C [27]. The data in Table 1 revealed an equilibrium solubility value of 12.4 μg/ml when determined in 0.1 N HCl, at 37°C (Table 1).…”
Section: Drug Content and Equilibrium Solubilitymentioning
confidence: 94%
“…The aqueous solubility of itraconazole at ambient temperature and neutral pH was recoded to be around 1 ng/ml. The solubility was found to undergo significant increase in acidic solution reaching 4 μg/ml in 0.1 N HCl at 25°C [27]. The data in Table 1 revealed an equilibrium solubility value of 12.4 μg/ml when determined in 0.1 N HCl, at 37°C (Table 1).…”
Section: Drug Content and Equilibrium Solubilitymentioning
confidence: 94%
“…Thus, itraconazole appears to be a suitable candidate. Clinical investigations has already indicated that application of 5 g of a 2% itraconazole cream was very well tolerated and the drug was not systemically absorbed (Francois et al, 2003). As per the previous discussion, it was also worthy to use itraconazole for a successful development of VDDS considering its pK a (5.6) and normal vaginal pH (4-5).…”
Section: Selection Of Drug Candidatementioning
confidence: 82%
“…Then, the required amounts 2%, 4% and 8% w/w of the LPE was added to make a proper formula having the best anti-inflammatory activity. Finally the best percentage of the LPE extract was determined and physicochemical stabilities were evaluated [19].…”
Section: Cream Preparationmentioning
confidence: 99%